A phase 2, single‐arm study of ramucirumab in patients with metastatic renal cell carcinoma with disease progression on or intolerance to tyrosine kinase inhibitor therapy. Issue 11 (27th February 2014) - Garcia, Jorge A.; Hudes, Gary R.; Choueiri, Toni K.; Stadler, Walter M.; Wood, Laura S.; Gurtler, Jayne; Bhatia, Shailender; Joshi, Adarsh; Hozak, Rebecca R.; Xu, Yihuan; Schwartz, Jonathan D.; Thompson, John A.
Abstract : BACKGROUND: Multitargeted tyrosine kinase inhibitors (TKIs) have antitumor activity in metastatic renal cell carcinoma (mRCC). Resistance to these agents develops frequently, and their use is often limited by intolerance. Ramucirumab is a recombinant human monoclonal antibody directed against human vascular endothelial growth factor receptor‐2. For this study, the authors investigated the clinical efficacy and safety of ramucirumab in patients with TKI‐resistant/intolerant mRCC. METHODS: In this single‐arm phase 2 trial, patients received ramucirumab 8 mg/kg every 2 weeks until they developed disease progression or intolerable toxicity. The primary endpoint was the best objective response rate (ORR); additional endpoints included the disease control rate (DCR), progression‐free survival (PFS), the median duration of overall response, and safety. RESULTS: Thirty‐nine patients with RCC received ramucirumab monotherapy. Prior TKI therapy included sunitinib (59% of patients), sunitinib and sorafenib (30.8% of patients), and sorafenib (10.3% of patients). The ORR was 5.1% (95% confidence interval [CI], 0.6%‐17.3%). The 12‐week DCR was 64.1% (95% CI, 47.2%‐78.8%). The median PFS was 7.1 months (95% CI, 4.1‐9.7 months), and the median overall survival was 24.8 months (95% CI, 18.9‐32.6 months). Grade 3 or higher adverse events that occurred in ≥5% of patients included grade 3 hypertension (7.7%) and proteinuria (5.1%). There was 1 on‐study death from multiorgan failure. CONCLUSIONS: Although the study did not meet its primary endpoint of ≥15% ORR, ramucirumab was associated with evidence of antitumor activity in patients with TKI‐resistant/intolerant mRCC. Ramucirumab was safe and well tolerated. Cancer 2014;120:1647–1655 . © 2014 American Cancer Society . Abstract : In this single‐arm, phase 2 trial, ramucirumab monotherapy had a limited impact on the Response Evaluation Criteria in Solid Tumors–defined response of patients with metastatic renal cell carcinoma who either had progression on or developed drug intolerance to vascular endothelial growth factor receptor inhibitory tyrosine kinase inhibitors. However, the median and 1‐year progression‐free survival rates were encouraging, and ramucirumab was safe and well tolerated.